APPLICATION OF ERP SYSTEMS IN HIGHER EDUCATION FUNDRAISING - Nozdrina, Larysa; Krytovych , Olena (Socio-economic relations in the digital society, 2022)
The article describes the theoretical and methodological approaches to digitalization of fundraising activities of higher education using ERP systems. The essence of fundraising and its features in higher educational institutions in the conditions of digitalization are considered. The principles of using ERP systems as a tool for the digitalization of fundraising are described. It is proved that for the financial autonomy of a higher education institution it is necessary to carry out fundraising activities to ensure competitiveness in the market of educational services. The article proposes approaches to the use of modern ERP system BJet in the fundraising department of the University of Banking during the implementation of the project Veteran Start-Up Education. The main advantages of the Bjet ERP system include 24/7 management; Comprehensive solution; Convenient interface; Use of templates; Separation of access; Fast data recovery; Interaction with other systems; Adaptive cost; Fast integration; Library of 400 modules. Features of using Bjet are storing large amounts of information about students, teachers, schedules, exams and other data in a single system, in-depth analytics using dashboards, providing communication with all stakeholders of projects and more. Such integration facilitates automation, reduces data duplication, and allows participants and trainers to interact with each other, and thus facilitate project planning and management processes in the fundraising department of the higher education institution.It is proposed to implement the Veteran Start-up Education project in the Bjet ERP system using the OpenEduCat software solution developed for educational institutions. In turn, the implementation of the project in the Bjet system includes the creation of: 1) a base of students and trainers of the project; 3) training schedules; 4) tasks for self-study and practical training; 5) filling the project costs; 6) formation of reports and dashboards. After creating a schedule for each training module, a ready-made schedule in the form of a kanban board is formed.
Keywords: high school; fundraising; digitalization; ERP-system; BJet; project